Raising Healthy Children: Family Fitness - Lisa D. Chan; Karla P. Shelnutt (EDIS)
FCS8892, a 3-page illustrated fact sheet by Lisa D. Chan and Karla P. Shelnutt, addresses the obesity epidemic, the benefits of physical activity for children and adults and how to work physical activity into family lifestyle. Published by the UF Department of Family Youth and Community Sciences, January 2010.